1992
DOI: 10.1073/pnas.89.9.3676
|View full text |Cite
|
Sign up to set email alerts
|

Netropsin specifically enhances RNA polymerase II termination at terminator sites in vitro.

Abstract: We describe an in vitro system that emulates the specific and efficient transcriptional termination associated with the human gastrin gene terminator in vivo. The system involves a dC-tailed DNA template containing the gastrin gene terminator sequence, purified RNA polymerase II, and purified elongation factor TFIIS. In this system, the basal level of termination by RNA polymerase II at the gastrin gene terminator is specifically enhanced by netropsin, an (A+T)-rich minor groove-binding peptide. This enhanced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1996
1996
2003
2003

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Computational studies have contributed information that provides a rational explanation for the selective fit of these crescent-shaped ligands into the minor groove of DNA (26,27). Thermodynamic studies of Net and Dst binding to DNA, and their effects on the formation of protein/DNA complexes, have also been thoroughly investigated (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). Since the pioneer discoveries of the AT-selective binding of Net and Dst to DNA (41), a considerable number of physicochemical, biochemical, and biological studies have been reported to increase ous understanding of the details of the mechanisms by which these two antibiotics bind to and recognize double-stranded DNA squence (42).…”
mentioning
confidence: 99%
“…Computational studies have contributed information that provides a rational explanation for the selective fit of these crescent-shaped ligands into the minor groove of DNA (26,27). Thermodynamic studies of Net and Dst binding to DNA, and their effects on the formation of protein/DNA complexes, have also been thoroughly investigated (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). Since the pioneer discoveries of the AT-selective binding of Net and Dst to DNA (41), a considerable number of physicochemical, biochemical, and biological studies have been reported to increase ous understanding of the details of the mechanisms by which these two antibiotics bind to and recognize double-stranded DNA squence (42).…”
mentioning
confidence: 99%
“…The 3′‐end region of the human gastrin gene (GeneBank accession no. M12929) has been extensively studied (79), and the positions of three important DNA elements (polyadenylation signal, cleavage site, and transcriptional terminator) were identified (Figure 1A). To examine the effects of the transcriptional terminator element on the expression of the cloned genes, a series of expression plasmids were constructed using the commercially available vector, pSV‐β‐gal, as a basic vector (Figure 1B; see Materials and Methods) and transfected into HeLa cells.…”
Section: Resultsmentioning
confidence: 99%
“…However, little information is available on the transcriptional terminator elements where RNA polymerases actually stop synthesizing mRNAs. Although a consensus sequence has been identified in the terminal region of nine eukaryotic genes (6), the only transcription terminator functionally identified so far is the one existing at the 3′‐end region of the human gastrin gene (79). Here we report that the application of the transcriptional terminator element of the human gastrin gene to a mammalian expression system enhances the transient expressions of the cloned genes.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated in Vitro that these compounds inhibit many DNA-dependent enzymatic functions associated with DNA replication or RNA transcription. Enzymes affected include DNA and RNA polymerases and topoisomerases (Puschendorf & Grunicke, 1969;Zimmer et al, 1971b;Wahnert et al, 1975;Woynarowski et al, 1989;Mortensen et al, 1990;McHugh et al, 1990;Ueno et al, 1992), as well as DNA gyrase and helicase (Bachur et al, 1993;Storl et al, 1993). Recent studies, moreover, have illustrated the ability of these groove-binding drugs to prevent the binding of transcription factors (Gambari et al, 1991;Dorn et al, 1992;Chiang et al, 1994;Welch et al, 1994).…”
mentioning
confidence: 99%